Pengaruh Gaya Kepemimpinan dan Penilaian Kerja Terhadap Kepuasan Kerja Serta Implikasinya Pada Kinerja Karyawan PT. Waskita Karya Proyek Jalan Tol Serpong – Cinere - Surya Dwi Gumilang; Rosmegawati Rosmegawati (Jurnal Manajemen FE-UB, 2024)
This study aims to examine and analyze the influence of factors related to Employee Performance. These factors include Leadership Style and Job Assessment, which subsequently functioned as independent variables which influence Employee Performance as a dependent variable, while Job Satisfaction is a variable that functions as an Intervening variable. The research method used in this study is path analysis. Research results show that there is a direct influence of leadership style and job assessment both simultaneously and partially on job satisfaction. Leadership style, job assessment and job satisfaction have a direct effect on employee performance both simultaneously and partially. Job satisfaction as an intervening variable is able to mediate the indirect influence of leadership style and work assessment on employee performance, with the results of the suitability test of a decent model.